Complaints, Endoscopic and Histopathological Findings in Children with Helicobacter pylori Infection: Are There Any Correlations with Each Other? - Günsel Kutluk; Esra Polat; Muharrem Çiçek; Tuğçe Kalaycı Oral; Şeyma Murtezaoğlu Karatekin; Nermin Gündüz (Galenos Publishing House, 2023)
Objective: There is no significant clinical manifestations indicating Helicobacter pylori (H. pylori) infection in pediatric population. In this study, the most common complaints, endoscopic and histopathological findings in children with H. pylori infection were evaluated and their correlation with each other was explicated. Method: Patients between 3-18 years, who had documented H. pylori infection, were enrolled in this study. Gastric biopsies were taken in all patients for rapid urease test (RUT) and histopathological examination, activity of gastritis, chronic inflammation, and Sydney classification was used to evaluate intensity of H. pylori, grade of atrophy, and intestinal metaplasia. Demographic characteristics, complaints, endoscopic findings and Sydney scores of the patients were recorded. Results: A total of 339 patients (183 females) were enrolled in the study. The most common complaints were dyspepsia and epigastric pain. Ninety percent of the patients had antral pathology, including antral nodularity in 78% of the cases. Relation between dyspepsia, epigastric pain, and antral nodularity was found to be statistically significant. In histopathological examination, intensity of H. pylori is found to be increasing with age. RUT was positive in 89.4% of the patients and relation between RUT results and the intensity of H. pylori was statistically significant. Highly significant correlations were detected between macroscopic changes in the antrum, the intensity of H. pylori and gastritis activity (p≤0.0001, p=0.01, respectively). Conclusion: The most common complaints of children with H. pylori infection were epigastric pain and dyspepsia. There were significant relations with these complaints, antral macroscopic changes and intensity of H. pylori, which increases with age. As a result, dyspepsia and epigastric pain are related with antral changes. Considering that antral changes are also associated with H. pylori intensity, gastritis activity and chronic inflammation, early eradication of the H. pylori infection can be recommended to prevent long-term complications in children with H. pylori infection.